2020
DOI: 10.3390/antibiotics9060305
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Nisin Derivative M17Q Has Enhanced Activity against Staphylococcus epidermidis

Abstract: Staphylococcus epidermidis is frequently implicated in medical device-related infections. As a result of this, novel approaches for control of this opportunistic pathogen are required. We examined the ability of the natural peptide nisin A, produced by Lactococcus lactis, to inhibit S. epidermidis. In addition, a bank of 29 rationally selected bioengineered L. lactis strains were examined with the aim of identifying a nisin derivative with enhanced antimicrobial activity. Agar-based deferred antagonism assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…decreased the count of the gram positive Staphylococcus sciuri, while Escherichia coli, molds and yeasts were increased. The great activity of this bacteriocin; Nisin was recorded by many researchers [27][28][29][30][31]. The arising count of gram negative bacteria and mycotic growth may be organized by the nutritional competition among microbial populations [32].…”
Section: Discussionmentioning
confidence: 98%
“…decreased the count of the gram positive Staphylococcus sciuri, while Escherichia coli, molds and yeasts were increased. The great activity of this bacteriocin; Nisin was recorded by many researchers [27][28][29][30][31]. The arising count of gram negative bacteria and mycotic growth may be organized by the nutritional competition among microbial populations [32].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, investigations that involved the in vivo incorporation of tryptophan analogues into nisin in a bid to yield improved or altered-specificity variants revealed that M17W displayed 17-fold less activity than parental nisin A [23]. More recently, a study has demonstrated the enhanced specific activity of nisin A M17Q over nisin A against clinical strains of S. epidermidis, revealing it to be superior at reducing biofilm production on medical device substrates and at reducing bacterial numbers in a simulated wound fluid [37]. The contrasting sensitivity of mastitis-associated S. aureus and industrially relevant lactococci to nisin A M17Q, nisin A T2L and nisin A HTK provides additional data that some bioengineered nisin derivatives exhibit target-specific variations in potency.…”
Section: Discussionmentioning
confidence: 99%
“…e stationary microtiter plate method can be used to assess the biofilm growth of target strains [56,77,128,129] (see Protocol S12and Figure S10of the Supplementary Material).…”
Section: Model Food Trialsmentioning
confidence: 99%
“…is assay has successfully demonstrated that nisin A and its bioengineered derivatives can reduce the formation of biofilm both on plastic and medical device material surfaces [56,77,128,129].…”
Section: Model Food Trialsmentioning
confidence: 99%
See 1 more Smart Citation